2006
DOI: 10.1017/s0022112006008779
|View full text |Cite
|
Sign up to set email alerts
|

Experiments at a two-scale dynamo test facility

Abstract: A report of experimental results on dynamo action is presented, obtained at the Karlsruhe dynamo test facility. Former observations concerning the properties of the dynamo magnetic field are corroborated and complemented. The feedback of the dynamo magnetic field on the sodium velocity in the test module is analysed based on measurements employing permanent magnet potential sensors. The evaluation of time signals recorded by these probes shows that a growing dynamo magnetic field transforms hydrodynamic turbul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 28 publications
0
17
0
Order By: Relevance
“…5,6 Since then, a number of experiments have been carried out at both places providing a wealth of data on the dynamo behavior in the kinematic and the saturation regime. [7][8][9][10][11][12][13][14][15][16][17][18] Further dynamorelated experiments are being prepared or carried out at various places in the world. [19][20][21][22][23] Although, up to present, they have not yet reached the self-excitation condition, they have brought about many interesting results, in particular concerning the role of turbulence in flows with large Re m .…”
Section: Introductionmentioning
confidence: 99%
“…5,6 Since then, a number of experiments have been carried out at both places providing a wealth of data on the dynamo behavior in the kinematic and the saturation regime. [7][8][9][10][11][12][13][14][15][16][17][18] Further dynamorelated experiments are being prepared or carried out at various places in the world. [19][20][21][22][23] Although, up to present, they have not yet reached the self-excitation condition, they have brought about many interesting results, in particular concerning the role of turbulence in flows with large Re m .…”
Section: Introductionmentioning
confidence: 99%
“…The magnetic field generated is of dipolar character, oriented perpendicular to the axis of the spin generators ('an equatorial dipole'). Measurement of the pressure and flow rates in the channels indicates an additional dissipation above onset which varies linearly with the flow rate, with an order of magnitude of about 10 kW at 10% over threshold (Müller et al 2006(Müller et al , 2008. As the dynamo field grows, a reduction of the flow velocity in the spin generators is also observed, however, the detailed mechanisms of the saturation of the instability are not known.…”
Section: The Karlsruhe Experimentsmentioning
confidence: 99%
“…In practice each of the 52 helical vortex generators is made of 2 concentric channels: one in which the flow is purely axial, and a surrounding one in which the fluid is guided in helical motion. A very comprehensive review of the experiment and its findings can be found in Müller et al (2006). Dynamo action was obtained for critical values of the magnetic Reynolds number Rm c = α ⊥ L/λ ∈ [8.4, 9.3] (here the α parameter is used as a velocity characteristic scale, and L is the overall cross-section of the experiment).…”
Section: The Karlsruhe Experimentsmentioning
confidence: 99%
“…The local sodium velocity was measured in the center of one of the four axial channels located next to the axis of the module. This was done with the help of a permanent magnet potential probe (PMP) whose technical details have been described in Müller et al [23]. A more detailed description of the overall experimental set-up, the sodium technologies and first results may be taken from reports by Stieglitz and Müller [25][26][27].…”
Section: The Design Of the Test Facilitymentioning
confidence: 99%
“…From the recorded voltage signal of the probe the local velocity in the center of the channel was determined (see Müller et al [23]). The measured relative local velocity, presented in Fig.…”
Section: Back-reaction and Joule Dissipationmentioning
confidence: 99%